Gender characteristics of the physical development of the head (Review article) - Khabilova Shahzoda Muzaffar qizi; Ashurov Tolkin Abdulaevich (Zien Journals, 2024)
Indicators of physical development are anthropometric data, the rate of their change in the process of growth, harmonious development, the ratio of calendar and biological age, constitutional features. Assessment of the physical development of the child population based on anthropometric data is one of the key indicators of the health of the child population and is important for doctors, teachers and sports trainers. In scientific anthropometry, when determining the type of face and shape of the head, anthropometric points are used, which are divided into craniometric, that is, their landmarks are on the bones of the skull, and cephalometric - landmarks are on the soft tissues of the head.
Keywords: physical development; anthropometry; head